Association of soluble suppression of tumorigenicity 2 protein with new-onset atrial fibrillation in patients with acute ST-segment elevation myocardial infarction undergoing primary PCI - Zhao, Ting-ting; Pan, Tian-jiao; Yang, Yi-bo; Pei, Xiao-yang; Wang, Yong (Frontiers in Cardiovascular Medicine, 2023)
Background: Studies have suggested that soluble suppression of tumorigenicity 2 protein (sST2) is associated with new-onset atrial fibrillation (NOAF) in patients with coronary artery disease (CAD).However, the predictive value of sST2 in patients with acute ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI) has not been well studied.Methods: A total of 580 patients with STEMI undergoing primary PCI were consecutively recruited between January 2021 and January 2023 and divided into the NOAF and no NOAF groups based on the presence of NOAF during admission. The concentration of sST2 in blood samples was measured in all individuals. The clinical data of the two groups were prospectively analyzed to explore the predictive factors of NOAF in patients with STEMI undergoing primary PCI.Results: A total of 41 (7.1%) patients developed NOAF. NOAF was associated with age, diabetes mellitus, hypertension, the left atrial (LA) diameter, N-terminal pro-brain natriuretic peptide, Creactive protein (CRP), sST2, a Killip class ≥ 2, and a final TIMI flow grade < 3. After multiple factors were included, LA diameter, CRP, sST2, a Killip class ≥ 2, and a final TIMI flow grade < 3 were still risk factors for NOAF. The receiver operating characteristic (ROC) curve showed the following: 1) when the LA diameter was > 38.5 mm, the sensitivity and specificity were 67.2% and 68.2%, respectively. and the area under the ROC curve (AUC) was 0.683 (95% confidence interval[CI]: 0.545-0.732; p = 0.003); 2) when CRP was > 8.59, the sensitivity and specificity were 68.6% and 69.2%, respectively, and the AUC was 0.713 (95% CI: 0.621-0.778; p < 0.001); and 3) when sST2 was > 53.3, the sensitivity and specificity were 79.2% and 68.7%, respectively, and the AUC was 0.799 (95% CI: 0.675-0.865; p < 0.001).sST2 is an independent predictor of NOAF in patients with STEMI undergoing PCI.